2020
DOI: 10.3399/bjgp20x710153
|View full text |Cite
|
Sign up to set email alerts
|

Delegating home visits in general practice: a realist review on the impact on GP workload and patient care

Abstract: BackgroundUK general practice is being shaped by new ways of working. Traditional GP tasks are being delegated to other staff with the intention of reducing GPs’ workload and hospital admissions, and improving patients’ access to care. One such task is patient-requested home visits. However, it is unclear what impact delegated home visits may have, who might benefit, and under what circumstances.AimTo expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…In four of the five included reviews, data extracted from published, academic research papers dominate. However, in one review (Review A), only 51% of included papers fell into this category, 44 and in one other (Review E) these documents made up only 24% of included documents 46 . All of the reviews included data extracted from numerous other types of document, in varying proportions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In four of the five included reviews, data extracted from published, academic research papers dominate. However, in one review (Review A), only 51% of included papers fell into this category, 44 and in one other (Review E) these documents made up only 24% of included documents 46 . All of the reviews included data extracted from numerous other types of document, in varying proportions.…”
Section: Resultsmentioning
confidence: 99%
“…The lead reviewers on each project agreed to contribute their data to this study. The detailed methods employed in each review are reported in their own study protocols and published reports (where applicable) 39–48 . For this study, we collected data from each review team relating to the final list of documents included in each review.…”
Section: Methodsmentioning
confidence: 99%
“…The initial uncertainty described by GPs was mitigated by practices having the opportunity to define the scope of the ECP's work, such as triage decisions and interdisciplinary learning, which is also an important feature of integrating nurse practitioners into primary care teams [10]. Collaboration between GPs and ECPs was another essential factor that mitigated the potential for professional role boundary conflicts [10,11,20]. As previously described for interdisciplinary working between physician associates and GPs [13], ECPs and GPs worked together to define their roles and reframe their professional boundaries at the GP practice level.…”
Section: Links With the Existing Evidence Basementioning
confidence: 99%
“…11 As the delegation of home visits develops, practioners will need clarity around boundaries and understanding of roles. 12 Therefore, a blended model of home visits may be appropriate with acute presentations being delegated to paramedics or advanced nurse practioners. Long-term conditions or more complex Far End cases may be best retained by the GP until the evidence base and ways to implement recommendations have been established.…”
Section: Home Visits or House Calls?mentioning
confidence: 99%